Deteriorated corrosion performance of micro-alloyed Mg-Zn alloy after heat treatment and mechanical processing. (30th November 2021) - Jin, Yiming; Blawert, Carsten; Yang, Hong; Wiese, Björn; Bohlen, Jan; Mei, Di; Deng, Min; Feyerabend, Frank; Willumeit, Regine
Highlights: ppm level Fe/Si deteriorate the corrosion performance of Mg-0.5Zn after heat treatment. Longer heat treatment induces Fe-Si particle with higher concentration of Fe. Fast cooling rate and short heat treatment are important in micro-alloying Mg systems. Corrosion resistance loss induced by Fe-Si particles is not compensated by further extrusion. Abstract: The corrosion performances of the as-cast and solution-treated Mg-0.5Zn samples were investigated in 0.9% NaCl solution and compared. From the electrochemical measurement results and corrosion morphology observations, it is found that the corrosion resistance of Mg-0.5Zn deteriorated with the extension of solution treatment duration. The main reason was the formation of Fe-Si precipitates with higher Fe concentrations during heat treatment. The Fe-Si precipitates, especially the ones with high Fe contents influenced the corrosion initiation and propagation significantly. In regard of corrosion performance, the solution-treated and then extruded sample was also performing not as good as the cast and then directly extruded sample. Graphical abstract: Image, graphical abstract